Bronchopulmonary dysplasia in children: contemporary diagnosis, consequences and their treatment (update 2017) - M.O. Gonchar; G.S. Senatorova; O.L. Logvinova; G.R. Muratov (Zaslavsky O.Yu., 2017)
The article deals with the modern principles of diagnosing bronchopulmonary dysplasia (BPD) in children based on the guidelines of the American Thoracic and European Respiratory Societies. The article have aim to provide an optimal patient management. In modern world literature, BPD is considered as a diffuse parenchymal lung disease of preterm infants that require artificial ventilation and oxygen therapy for acute respiratory failure in the neonatal period. The form and degree of bronchopulmonary dysplasia severity are determined by the overall duration of oxygen dependence and gestational age. In infants, the disease can run with respiratory dysfunction, respiratory failure, asthma-like syndrome, increased susceptibility to respiratory infections, tobacco smoke, and pollutants. Some children with BPD have low tolerance to physical activity with hypersensitivity to hypoxia. 25-37 % of patients have pulmonary arterial hypertension. The article is focused on which should be paid attention when specifying the anamnesis of life and disease in the parents of the child. Current monitoring of the disease includes examination, evaluation of laboratory and instrumental studies. Analysis of the fibrobronchoscopy and bodipletismography data has the weak recommendation. Eliminating hypoxia, optimizing the nutritive status, determining the presence of an open arterial duct, specific drug therapy, and the use of vasodilators should be paid attention when treating a child with bronchopulmonary dysplasia. The article presents a chart for the monitoring of a child with BPD and indications for hospitalization of the patient, expediency and usefulness necessary for practicing pediatricians, family doctors, pediatric pulmonologists.